2019
DOI: 10.3390/ijms20020399
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Solid Lipid Curcumin Particles Induce Autophagy, but Inhibit Mitophagy and the PI3K-Akt/mTOR Pathway in Cultured Glioblastoma Cells

Abstract: Autophagy and the (PI3K-Akt/mTOR) signaling pathway play significant roles in glioblastoma multiforme (GBM) cell death and survival. Curcumin (Cur) has been reported to prevent several cancers, including GBM. However, the poor solubility and limited bioavailability of natural Cur limits its application in preventing GBM growth. Previously, we have shown the greater apoptotic and anti-carcinogenic effects of solid lipid Cur particles (SLCP) than natural Cur in cultured GBM cells. Here, we compared the autophagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 60 publications
3
60
0
1
Order By: Relevance
“…Moreover, curcumin treatment in A172 human glioblastoma cells leads to cell death by inducing autophagy flux [84]. Another study confirmed that curcumin promotes autophagy in glioblastoma cells while it inhibits mitophagy [85]. Curcumin also blocks invasion and migration potential of glioblastoma U87 cells by decreasing the expression of fascin, an actin-binding protein involved in migration and invasion [86].…”
Section: Curcumin Effects On Central Nervous System Cancersmentioning
confidence: 91%
“…Moreover, curcumin treatment in A172 human glioblastoma cells leads to cell death by inducing autophagy flux [84]. Another study confirmed that curcumin promotes autophagy in glioblastoma cells while it inhibits mitophagy [85]. Curcumin also blocks invasion and migration potential of glioblastoma U87 cells by decreasing the expression of fascin, an actin-binding protein involved in migration and invasion [86].…”
Section: Curcumin Effects On Central Nervous System Cancersmentioning
confidence: 91%
“…In addition, cell survival markers were downregulated and cell death markers were upregulated by curcumin. All these effects were amplified in SLCP-treated cells in comparison to curcumin-treated cells [50].…”
Section: Cancermentioning
confidence: 93%
“…To compare the anti-amyloid potency, such as inhibition of Aβ42 aggregation after treatment with SLCP and natural Cur, the dot blot assay was performed, as described previously [50,51]. Brie y, Aβ42 peptide was dissolved in hexa uoro isopropanol (HFIP), mixed for 1 min and allowed to solubilize for 30 min at room temperature, and then the HFIP was evaporated under laminar hood to make a thin lm of peptide layer.…”
Section: Dot Blot Assaymentioning
confidence: 99%
“…buffer and a protease inhibitor cocktail (Sigma, Catalog no: P8340-5ML), as described previously [18,47,51]. The tissue homogenate was centrifuged at 13,300 rpm for 20 min at 4 o C, and the supernatant was collected, aliquoted with 20 µL in each PCR-tube and stored at -80 o C until needed.…”
Section: 2mentioning
confidence: 99%